ANALYSIS OF EFFECT OF MICROWAVE IRRADIATION IN FUNCTIONAL GROUP OF ZEOLITE SYNTHESIS - puput eka Suryani (Jurnal Ilmiah Teknosains, 2017)
Zeolite is a multifunctional material that is often used in industry as catalyst, ion exchange, adsorber, etc. Nowadays many researchers have studied and developed the synthesis technique of zeolite using new energy like microwave. Microwave irradiation has been shown to be more efficient when applied to chemical or physical processes. In this research will be studied the effect of microwave usage on zeolite characteristic that is produced by functional group at zeolite. Based on FTIR analysis on synthetic zeolite samples from rice husk ash using microwave irradiation modification, it can be concluded that the increase in absorbance occurs in samples with modification. This is evident in some functional groups such as Si-OH and Si-O-Al at wavelengths of 3450 cm-1 and 1000.35 cm-1. So it can be concluded that microwave irradiation can improve the reaction process in synthetic zeolite preparation.